FORMGIVING - Ingels, Bjarke, author 525575; BIG Bjarke Ingels Group 525576 (Köln : Taschen, 2020)
"Formgiving. An Architectural Future History, the new book by BIG (Bjarke Ingels Group), and the latest installment in its TASCHEN trilogy, is a visionary attempt to look at the horizon of time, from the Big Bang into the most distant future. The volume addresses six evolutionary trajectories, and the development of artificial intelligence, sustainability, interplanetary migration, among others, in the context of architecture and design, in order to give form to the future world we want to inhabit--right now.